Teachers’ Pedagogical Reasoning and Action in Technical and Vocational Education - Mohamad, Mimi Mohaffyza; Heong, Yee Mei; Kiong, Tee Tze; Ibrahim Mukhtar, Marina; Ahmad, Adnan (Journal of Technical Education and Training, 2019)
Model Pedagogical Reasoning and Action (MPRA) is the process of teaching in the aspects of understanding, transformation, evaluation and assessment, reflection of teaching and understanding of new knowledge and competency of teachers. The survey was conducted on teachers of technical and vocational teaching practices in identifying the teaching practices through the process proposed by MPRA. The objectives of the study were to identify the level of knowledge and competencies of teaching, the differences of practices according to different technical and vocational subject and also the relationship based on the teachers’ demographic such as teaching experiences, courses attended and skills’ certificate. The quantitative approach through a set of questionnaire distributed to relevant teachers. The respondents involved teachers of technical and vocational teachers from various fields. 160 teachers from eight areas of technical and vocational subjects involved as respondents by using convenience sampling techniques. The findings demonstrate a level of competency and knowledge of teachers are at a high level. There have been differences of practice teaching according to the field and significant relationship between competency and knowledge with teaching experience. As a result, any model of teaching or pedagogical approach, teachers are able to apply their knowledge and skills in teaching and working experience in industry also can contribute a broader interpretation of knowledge and teaching in effective strategies for technical and vocational education field.